Supporting Ecuadorian teachers in their classroom research: Reflections on becoming a research mentor - Erzsébet Ágnes Békés (English Language Teaching and Research Journal (ELTAR-J), 2020)
Classroom-based research has flourished in the past 15 years, often introduced institutionally, as part of teachers’ Continuous Professional Development. Supporting teachers in their classroom research requires facilitation and scaffolding. Therefore, teacher trainers are often assigned the tasks of research-mentoring. However, this activity requires special skills and sustained mentoring of the mentors themselves. Mentoring, as an activity, has a rich literature, but mentoring teachers, and more specifically, mentoring language teachers researching their classrooms has not been widely documented as yet. The present self-study constitutes a reflective account of an experienced teacher trainer’s journey into mentoring. By simultaneously taking part in an online mentoring course as well as putting the newly gained knowledge into practice, the author was able to mentor 11 English language teachers and 5 English major students that came together to carry out tasks related to mentoring action research projects and / or accomplish their own classroom research as required by the Ecuadorian state university where they teach or study. The self-study draws on the first three months of the year-long program, and presents the process of growing into the mentoring role by using the author’s reflective journal, email exchanges with her lead-mentor, posts on the online EVO Mentoring course and feedback from participants. The author concludes that mentoring teacher-researchers is a two-way activity that benefits both the mentor and the mentee, but the value of mentoring should be acknowledged institutionally, and its practice extended.